Development of a Chromatography Textbook Based on Project-Based Learning Using an Ethnoscience Approach with Augmented Reality - Hanisah Hasibuan; Sri A. Sari; Marudut Sinaga (Jurnal Akademika Kimia, 2026)
Advances in chemistry during the Fourth Industrial Revolution demand learning that integrates concept mastery with 21st-century skills, yet current materials rarely combine local wisdom and digital technology. This study aimed to develop a chromatography textbook based on Project-Based Learning (PjBL), using an ethnoscience approach and Augmented Reality (AR), suitable for learning. The Research and Development (R&D) method, using the 4D model (Define, Design, Develop, Disseminate), was employed. The pilot study involved 20 Chemistry Education students, with expert validation sheets and student response questionnaires as instruments. The results of the expert validation indicated that this textbook is highly suitable, with an average content suitability percentage of 93.75%, graphic suitability of 93.75%, presentation suitability of 94.84%, and linguistic suitability of 100%. A pilot test conducted on a small group revealed highly positive student responses, with an average score of 3.88 (97.02%). These findings imply that integrating PjBL, ethnoscience, and AR can effectively support contextual, student-centered, and technology-enhanced chemistry learning. In practice, this approach can serve as a model for developing innovative instructional materials for other chemistry topics and for supporting curriculum transformation toward 21st-century skills.